2021
DOI: 10.1097/moh.0000000000000678
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic state associated with preeclampsia

Abstract: Purpose of review Preeclampsia is a common complication of pregnancy and contributes significantly to maternal and fetal morbidity and mortality. A protective hypercoagulable state is often developed during late pregnancy and can evolve into a prothrombotic state in patients with preeclampsia. The underlying mechanism of this prothrombotic transition remains poorly understood. We discuss recent progress in understanding the pathophysiology of preeclampsia and associated prothrombotic state. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…It is suggested that unsuccessful transformation of uterine spiral arteries by trophoblasts in early pregnancy leads to poor placentation, causing hypoperfusion in the placental bed and fetal tissues, and as a result, placental factors released from the placenta into the maternal circulation lead to endothelial dysfunction, which is the main pathophysiology of preeclampsia 20 . This endothelial dysfunction creates a prothrombogenic predisposition and also increases the risk of thrombotic complications in these patients 21 .…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that unsuccessful transformation of uterine spiral arteries by trophoblasts in early pregnancy leads to poor placentation, causing hypoperfusion in the placental bed and fetal tissues, and as a result, placental factors released from the placenta into the maternal circulation lead to endothelial dysfunction, which is the main pathophysiology of preeclampsia 20 . This endothelial dysfunction creates a prothrombogenic predisposition and also increases the risk of thrombotic complications in these patients 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a notable reduction in the surface expression of L-selectin (CD62L) on CD15+ neutrophils, which correlates with immune activation in PE [31]. Studies have shown that NETs can induce platelet activation and a prothrombotic state during PE [28,32]. This body of evidence suggests that neutrophils are activated and potentially primed for NET release in PE, both in the microcirculation and periphery, contributing to a feedback loop involving inflammation and endothelial dysfunction.…”
Section: Activation Of Neutrophils In Pementioning
confidence: 99%
“…The majority of the modifications in coagulation result in hypercoagulability, which protects the mother from excessive bleeding after delivery or miscarriage [16]. Hypercoagulability, endothelial damage, and venous stasis all contribute to the prothrombotic state that is pregnancy [17]. This hypercoagulable state is the most important predictor of thrombosis during pregnancy.…”
Section: Hemostasis In Pregnancymentioning
confidence: 99%